Multimodality Imaging of Giant Right Coronary Aneurysm and Postsurgical Coronary Artery Inflammation. Issue 1 (7th July 2015) - Celeng, Csilla; Székely, László; Tóth, Attila; Dénes, Mónika; Csobay-Novák, Csaba; Bartykowszki, Andrea; Károlyi, Mihály; Vágó, Hajnalka; Szőke, Sándor; Coelho Filho, Otavio R.; Andréka, Péter; Merkely, Béla; et al.
Abstract : Supplemental Digital Content is available in the text.